Contribuição para a melhoria no desempenho ambiental de porcelanatos: Avaliação de Ciclo de Vida (ACV) e o uso de fundentes enérgicos - Contartesi, Flavia (2019)
Whether due to growing environmental awareness or legal and market requirements, the quest for sustainable development has leading to the need to improve processes and products. In this scenario, the general objective of the present work was to contribute to the improvement in the environmental performance of porcelain tile industries in Brazil, the third largest producer of ceramic tiles in the world, from two complementary stages. The first one, through the Life Cycle Assessment (LCA) bibliography of ceramic tiles developed in Brazil and in the world, aimed to identify the most critical stages of the manufacturing process and to raise peculiarities of the Brazilian reality. The results pointed to the firing stage as the main responsible for the environmental impacts and the use of the dry route as the most outstanding peculiarity of the Brazilian industry. From these results, the second stage aimed to contribute with proposals to reduce the most critical stage. In this context, it was proposed the reduction of the firing temperature, and consequently of the associated impacts, in porcelain tiles manufactured by dry route through the use of energetic fluxing agents. To try to predict the effects of the addition of fluxes on the behavior of the standard formulation during sintering the Fluegel viscosity model was used. The initial reduction target of 30 °C was reached for all fluxes used and exceeded in some. In the supply of alkaline earth oxide modifiers, the prediction was accurate, for alkaline, approximate. However, for borates the results differed considerably from those predicted by the model. The results showed a good correlation between the viscosity of the liquid phase and the firing temperature, suggesting that the formulations with the lowest firing temperature are able to densify without reaching viscosity as low as the standard.